Prospective multicentre study on azole resistance in Aspergillus isolates from surveillance cultures in haematological patients in Italy. (September 2020) - Prigitano, A.; Esposto, M.C.; Grancini, A.; Passera, M.; Paolucci, M.; Stanzani, M.; Sartor, A.; Candoni, A.; Pitzurra, L.; Innocenti, P.; Micozzi, A.; Cascio, G. Lo; et al.
Highlights: The prevalence of azole resistance was 1.3% in haematological patients. The itraconazole resistance rate was 1.48% considering Aspergillus, section Fumigati. Two cryptic azole-resistant species were identified, Aspergillus lentulus and Aspergillus awamori. Abstract: Objectives: This study was conducted to assess the prevalence of azole resistance in Aspergillus isolates from patients with haematological malignancies or who were undergoing haematopoietic stem cell transplantation and to identify the molecular mechanism of resistance. Methods: In this 28-month prospective study involving 18 Italian centres, Aspergillus isolates from surveillance cultures were collected and screened for azole resistance, and mutations in the cyp51A gene were identified. Resistant isolates were genotyped by microsatellite analysis, and the allelic profiles were compared with those of resistant environmental and clinical isolates from the same geographical area that had been previously genotyped. Results: There were 292 Aspergillus isolates collected from 228 patients. The isolates belonged mainly to the section Fumigati (45.9%), Nigri (20.9%), Flavi (16.8%) and Terrei (4.8%). Three isolates showed itraconazole resistance: Aspergillus fumigatus sensu stricto, Aspergillus lentulus (section Fumigati ) and Aspergillus awamori (section Nigri ). The itraconazole resistance rates were 1% and 1.48% considering all Aspergillus spp. isolates and the Aspergillus section Fumigati, respectively. The prevalence of azole resistance among all the patients was 1.3%. Among patients harbouring A. fumigatus sensu stricto isolates, the resistance rate was 0.79%. The A. fumigatus isolate, with the TR34 /L98H mutation, was genotypically distant from the environmental and clinical strains previously genotyped. Conclusions: In this study, the Aspergillus azole resistance rate was 1% (3/292). In addition to A. fumigatus sensu stricto, A. lentulus and A. awamori azole-resistant isolates were identified. Therefore, it is important have a correct identification at the species level to address a rapid therapy better, quickly understand the shift towards cryptic species and have an updated knowledge of the local epidemiology.